Translating the impact of internal and external factors in achieving the sustainable market competitiveness: the mediating role of management practices - Rehman, Fazal ur; Sein, Yee Yee; Dmytrenko, Denys (Univerzita Tomáše Bati ve Zlíně, 2023)
The trend of market competitiveness in light of internal and external factors among sustainable communities is quite rare. Despite relative efforts, prior studies still paid limited attention to evaluating the role of internal and external factors in achieving market competitiveness in view of management practices. Hence, this study aims to examine the impact of internal (firm innovation) and external (business environment, environmental policies) factors in achieving sustainable market competitiveness via management practices in sustainable communities. Data were derived from the World Bank Enterprise Survey 2019 for Greece and analyzed through Partial Least Square Structural Equation Modeling (PLS-SEM). The findings show that management practices mediate the relationship between internal and external factors and sustainable market competitiveness in sustainable communities. The findings also reveal that firm innovation, management practices, and business environment have a significant positive relationship with sustainable market competitiveness. Surprisingly, environmental policies have a positive but insignificant relationship with sustainable market competitiveness in sustainable communities. These useful insights would enable practitioners and policymakers to develop more expedient management strategies to boost sustainable market competitiveness among firms and improve their image in sustainable communities. Even prior studies have paid wide attention to the indicators of market competitiveness, but this is the first study to highlight the market competitiveness in these domains. In the end, we provide several practical implications to elucidate the marketing expert to improve the degree of firm innovation, attain market competitiveness, focus on environmental policies, bring perfection in the business environment, and enhance efficiency in management practices to provide better services among sustainable communities.
Překlad vlivu vnitřních a vnějších faktorů na dosažení udržitelné tržní konkurenceschopnosti: zprostředkovatelská role manažerských postupů
Keywords: Firm Innovation; Management Practices; Business Environment; Environmental Policies; Sustainable Market Competitiveness; Inovace firmy; Manažerské postupy; Podnikatelské prostředí; Environmentální politika; Udržitelná tržní konkurenceschopnost